Uma análise geográfica da paisagem da Praça da Matriz de Aparecida de Goiânia-GO - Braga, Cristina Barbosa (2025)
The landscape is constantly constructed and reconstructed by human action, according to the needs of society at a given time. With the emergence of cities, we notice this transformation more clearly. There are important elements that should be studied and analyzed based on research, questions and understandings related to the teaching of Geography, especially the teaching of geographic landscape, city and socio-spatial formation of the Praça da Matriz in Aparecida de Goiânia-GO and fieldwork. Studies were performed during the Professional Master's Degree in Teaching in Basic Education of the Stricto Sensu Graduate Program of CEPAE/UFG, from 2021 to 2024, which resulted in an educational product entitled: “Geographic landscape, utilization and occupation of Praça da Matriz in Aparecida de Goiânia - GO”. The didactic sequence was an activity organized by the teacher-researcher, with the aim of mediating knowledge in the classroom so that students have the possibility of having a meaningful learning; it was an interactive didactic sequence based on the joint construction of knowledge through dialogue and reflection, and on the students' previous knowledge. The didactic sequence was developed based on bibliographic research, data collection and field work. Students from a 2nd year high school class from a school in the State Education Network in Aparecida de Goiânia - GO took part. Interviews were also conducted with descendants and pioneers residents. The studies conducted and mediated by the researcher professor lead the students to understand the concept of geographic landscape, city and socio-spatial formation of the municipality of Aparecida de Goiânia. An analysis was made of the considerations of the research participants about their experiences in Praça da Matriz, in Aparecida de Goiânia. The methodology used by the researcher professor was qualitative action research, which takes into account social, economic, cognitive and emotional aspects and allows greater contact with the target audience and investigation of the research object. The bibliographic research was designed and based on theoretical concepts to better carry out the study, with the expectation of providing those interested in the study in question, especially teachers and students, with elements that help them to better understand the concepts of geographic landscape, city and socio-spatial construction of Aparecida de Goiânia, so that they can analyze the space with a geographic perspective based on lived experiences focusing on the construction of significant knowledge.